Building the Croatian Language Technologies Portal - Tadić, Marko (Array, 2001)
Designing a portal dedicated to the Language Technologies applicable to Croatian would make the linguistic research easier and more efficient, providing students, researchers and corporate users, as well as anyone interested in language technologies, with not only the better access to information, but also with a professional forum where they can interact with others. In November 2000, the Croatian Language Technologies Portal project initiated by the Institute of Linguistics was started under the auspices of the Croatian Ministry of Science and Technology. It is designed as the central reference point containing an extensive list of links to Croatian and international institutions and projects related to the natural language processing, as well as to computational linguistic tools. It also has interactive components: the search engine for the contemporary part of Croatian National Corpus. In final version it will include also discussion boards, news groups, etc.